(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2023)
Current digital game-based learning (DGBL) methods for teaching history require a significant outlay in information and communications technology (ICT). This, in effect, constitutes a significant obstacle in implementing DGBL in the South African and Zimbabwean school context. Most schools do not have the infrastructure to equip entire classes with gaming-capable computers or sufficient access to electricity or the internet. This paper investigates how access to DGBL can be improved in challenged teaching and learning contexts by designing a pedagogy that is more readily adaptable to challenges presented in South African and Zimbabwean classrooms. The research uses a design-based research design where compatibility issues of DGBL are analysed with the aim of developing a more integrated approach that is then tested and evaluated in order to redesign the approach. The primary research question was: “How can Game Based Learning techniques and traditional history pedagogy be integrated to promote the use of Napoleon Total War in Southern African secondary school history classrooms?” Two schools from South Africa and Zimbabwe were selected as research sites for the implementation of the solution. The interventions were specifically designed to operate with a minimum of ICT resources. The solution comprised a teaching approach that combined DGBL based on a single laptop and projector with the more traditional teaching methods that were observed during formal lesson observations prior to designing the intervention. The research concluded that Napoleon Total War could be used to successfully teach elements of local and international history curricula. The method demonstrated a positive effect on learner motivation and engagement and demonstrated the potential to support formal assessment through tangential learning and assessment tasks designed from DGBL lessons. The study is significant in that it presents a methodology that can be more readily grasped by in-service teachers as it does not require significant gaming expertise and can also be used to complement their own teaching styles and approaches. A shortcoming of immersive DGBL in history is that it can risk learners mistaking learning for entertainment. With an integrative approach, it is clear to learners that while the medium can be engaging, learning is the primary aim of a DGBL-enhanced lesson. Furthermore, the research demonstrated that collaboration between researchers and teachers is essential to render DGBL research of practicable value in the classroom.